Proceedings of the conference on advances in mechanical engineering (AIME-2006), Januari 20-21, 2006 - Conference on advances in mechanical engineering : (2006); Khan, R A; Jamia Millia Islamia. Faculty of Engineering & Technology. Mechanical Engineering Department (New Delhi : Ane Books India, 2006)
18